Effect of Polypropylene Grafted Maleic Anhydride (PP-G-MAH) on the Properties of Asphalt and its Mixture Modified With Recycled Polyethylene/Recycled Polypropylene (RPE/RPP) Blends - Zhang, Wencai; Hao, Xiaogang; Fan, Changxin; Zhang, Shuai; Ma, Dechong; Yu, Xiaofang; Fu, Zhaohua; Feng, Gongji (Frontiers in Materials, 2022)
In this study, a ternary blend modifier (TBM) was prepared with RPE, RPP, and various dosages of PP-g-MAH (i.e., 0%, 1%, 3%, 5%, 7%, and 9% by weight of RPE and RPP) by a twin-screw extruder. The performance of TBM (4% by weight of asphalt) modified asphalt was studied, with the increase of PP-g-MAH content, the penetration decreases gradually, but softening point and viscosity increases and ductility exists minimum value at 7% content, with the increasing of PP-g-MAH percentage, the dynamic rheological properties show that |G*| increases, while the δ and |G*|cosδ decrease, and the fatigue performance (|G*|sinδ) of TBM modified asphalt is worse than virgin asphalt. Dynamic stability test shows that TBM shows the prominent high-temperature properties of a modified (asphalt mixture. BBR test indicates that the m-value of asphalt modified with TBM does not fulfill the requirements (m-value>0.3) except at 5% and 7%, but the S meets the standard requirements (S < 300 MPa), and increases from 0% to 7%, then decreases slightly. In order to illuminate possible reasons, a chemical reaction (ester compounds generated) and physical twines of concerned polymer molecules were put forward, and the results were confirmed by infrared analysis.